Genotypic influence in the juvenile to adult transition in olive seedlings - Valverde, Pedro; Diez, Concepción Munoz; Deger, Rustu Efe; Barranco, Diego; Trapero, Carlos (Frontiers in Plant Science, 2024)
Olive breeding is a long process and any improvement in shortening the juvenile phase is highly desirable. In the present study, the effect of olive tree parents in different agronomic characteristics have been evaluated during four years in 520 olive genotypes generated from three different crosses in three different experimental fields, all located in Andalusia region, Spain. The crosses evaluated are ‘Arbosana’ x ‘Sikitita’ and its reciprocal, whose parents are characterized by being early bearers; and ‘Frantoio’ free pollinated, whose mother variety is characterized by having a long unproductive period. We studied plant height, distance and time to the first flowering, plant vigor and percentage of olive oil in the fruits. The findings reveal that progeny from ‘Arbosana’ and ‘Sikitita’ crosses, irrespective of the direction of the cross, exhibited a lower distance to flower, early bearing, reduced vigor and a lower percentage of olive oil in fruit compared to ‘Frantoio’ seedlings obtained from free pollination. Furthermore, no discernible differences were observed in the evaluated characteristics when comparing reciprocal crosses across the three fields in the four-years assessment period. Therefore, these results highlight the significance of planting height in reducing the evaluation period required in an olive breeding program and support the hypothesis that there is no maternal effect in the inheritance of the evaluated agronomic characteristics in olive trees.